Income disparities in cardiovascular health across the lifespan. (December 2016) - Martinson, Melissa L.; Teitler, Julien O.; Plaza, Rayven; Reichman, Nancy E.
Abstract: Using data from the 1999–2014 National Health and Nutrition Examination Survey (n ~ 46, 000), this study documents income disparities in the age patterning of cardiovascular conditions across the lifespan in the U.S. The conditions were assessed from laboratory test results, self-reports of medications used to treat specific conditions, and anthropometric measurements, allowing us to capture whether individuals at given ages had developed the various conditions, regardless of previous diagnosis and treatment. We found evidence of large income disparities in the presence of cardiovascular conditions and risk factors for females, smaller disparities in the same conditions for males, and few disparities that increased with age for either gender. Results were very similar when considering disparities by education instead of income. The findings suggest that the widening socioeconomic gradients in health over the lifespan found in many previous studies—which have generally focused on self-rated health, activity limitations, or diagnosed conditions—reflect, at least to some extent, differences in diagnosis, treatment, and management of health conditions rather than age-related differences in developing them. The findings also suggest that preventive healthcare is not an important source of socioeconomic disparities in cardiovascular health in the U.S., at least for men. The observed patterns of income disparities in cardiovascular conditions over the lifespan are more consistent with theories of early life conditions and the imprinting of health endowments and susceptibilities early in life than with cumulative life exposure or stress hypotheses. Highlights: Large income disparities in the presence of cardiovascular conditions and risk factors were found for females. Smaller disparities in the presence of the same conditions were found for males. For most cardiovascular conditions and risk factors, disparities did not increase with age for either gender.